The Politics of the Transition of the Hagia Sophia to a Mosque by President Recep Tayyip Erdogan (POLITEA, 2022)
Hagia Sophia is one of the UNESCO world heritage sites built by Emperor Justinian I which is a Basilica building in Istanbul Turkiye and is a conflict between two religions, namely Christianity and Islam. In 2020 a decision that shocked the world came from President Recep Tayyip Erdogan who turned the Hagia Sophia into a mosque that was previously a museum during the time of Mustafa Kemal Ataturk. This paper uses library research, which identifies data including books, journals, articles, and more. The results of the study explain that the status of Hagia Sophia in Istanbul belongs to Turkish state law, not international law, so the Turkish president has the right to change the status of Hagia Sophia into a mosque that was once a museum during the secular regime. Mustafa Kemal Ataturk and other countries should not protest the decision. that. that. According to research from the Istanbul Economic Research Institute last June, 46.9% of respondents agreed with the transformation of the Hagia Sophia into a mosque, while 38.8% of respondents refused and wanted the Hagia Sophia to remain a museum.